Case Report: Successful Treatment of Refractory Interstitial Lung Disease With Cyclosporine A and Pirfenidone in a Child With SLE - Deng, Linxia; Chen, Yaxian; Hu, Xiufen; Zhou, Jianhua; Zhang, Yu (Frontiers in Immunology, 2021)
Interstitial lung disease (ILD) as an initial manifestation of lupus is rare, especially in young children. Here, we report a case of a 3-year-old boy who presented with fever, shortness of breath, and facial erythema. Clinical examination suggested a diagnosis of active systemic lupus erythematosus (SLE) with butterfly rash, anemia, positive antinuclear antibody, positive anti-double-stranded DNA, and hypocomplementemia. On retrospective review of the patient’s records, multiple chest computed tomography (CT) images showed non-specific interstitial pneumonia + organizing pneumonia pattern, with no further autoimmune work-up during the visit to a respiratory department. In our opinion, persistent interstitial pneumonia may be a clue to connective tissue disease. The patient received steroid treatment for 1 year, and the radiological and immunological resolution was noted. However, he still suffered from cough and dyspnea. After a 1-year follow-up, he was hospitalized again for SLE relapse. While continuing corticosteroid therapy, the patient was given combination therapy consisting of cyclosporine A (CsA) and monthly-pulse cyclophosphamide for 6 months, and decreased proteinuria was noted. However, the patient’s respiratory symptoms and pulmonary radiologic findings did not improve significantly. With continued steroid therapy, the patient was started on a daily regimen of CsA and pirfenidone. Both drugs were sufficiently effective to allow gradual reduction of steroid dosage. After 2 years of treatment, marked improvements in symptoms, pulmonary function and chest CT images were observed. Our experience with this case emphasizes that prompt work-up for connective tissue disease (CTD) should be considered in young children with ILD, and pirfenidone might be a useful add-on therapy with immunosuppressive agents for refractory CTD-ILD in pediatric patients. Nevertheless, further clinical trials including larger numbers of patients need to assess the efficiency and safety of this combination therapy for refractory CTD-ILD.